Investigating Relationships Between Alcohol and Cannabis Use in an Online Survey of Cannabis Users: A Focus on Cannabinoid Content and Cannabis for Medical Purposes - Karoly, Hollis C.; Mueller, Raeghan L.; Andrade, Chrysta C.; Hutchison, Kent E. (Frontiers in Psychiatry, 2020)
Cannabis is commonly used among people who drink alcohol, but findings are mixed regarding the direction of this relationship. The type of cannabis used (high-cannabidiol [CBD] vs. high-delta-9tetrahydrocannabinol [THC]) and motives for use (i.e., whether cannabis is used to treat a medical condition) may influence the relationship between cannabis and drinking. Specifically, CBD has shown preclinical promise in reducing alcohol consumption, and medical cannabis users report using cannabis to reduce drinking. This study leverages survey data from cannabis users who drink alcohol (N=533). Respondents were categorized as using cannabis to treat (CTT) a medical condition or as individuals whose cannabis use is not intended to treat (NCTT) a medical condition and grouped based on the THC/CBD ratio of the flower or edible cannabis they typically use (e.g., “High-THC/CBD,” “Medium-THC/CBD” and “Low-THC/CBD”). The CTT group (n=412) reported drinking significantly less frequently than the NCTT group (n=121). Cannabinoid content of flower cannabis was associated with alcohol consumed on cannabis-use days, such that individuals in the High-THC/CBD group drink more on cannabis-use days compared to the Medium-THC/CBD group. Cannabinoid content of edible cannabis was associated with drinks per drinking occasion, such that the High-THC/CBD group consumed the most drinks and the Low-THC/CBD group consumed the fewest. For both edible and flower groupings, higher-THC/CBD cannabis was associated with more frequent co-use than lower-THC/CBD cannabis. Results suggest that whether someone uses cannabis to treat a medical condition may impact their drinking frequency, and the cannabinoid content in flower and edible cannabis impacts alcohol consumption.